CeO2-modified Cu electrode for efficient CO2 electroreduction to multi-carbon products. Issue 54 (December 2021) - Zhao, Ziyi; Li, Xiaotong; Wang, Jianghao; Lv, Xiangzhou; Wu, Hao Bin
Graphical abstract: Highlights: A facile method of coating CeO2 nanoparticles on Cu was found to induce oxidative corrosion of the Cu electrode and form CeO2 -Cu interface. The CeO2 -modifed Cu electrode shown largely enhanced C2+ selectivity and suppressed H2 evolution during CO2 electroreduction. The optimal CeO2 -modified Cu electrode delivered a high C2+ Faradaic efficiency of 61 % and exhibits good stability for over 9 h. Abstract: Electrochemical reduction of carbon dioxide to value-added fuels offers a promising method to solve increasingly serious environmental problems and alleviate energy crisis. Herein, we report a facile method by coating Cu electrode with CeO2 nanoparticles to largely enhance the C2+ products selectivity during CO2 electroreduction. The Faradaic efficiency of C2+ products for optimal CeO2 -coated Cu electrode reached a high value of 61 % at -1.05 V vs RHE, and exhibited good stability for over 9 h of CO2 electrolysis. The CeO2 nanoparticles were found to induce oxidative corrosion of the Cu foil, leading to a CuO x layer in contact with the CeO2 nanoparticles. The interface between CeO2 nanoparticles and oxide-derived Cu might be attributed to the enhanced catalytic activity for C2+ products by promoting the CC coupling process.